Nutritional Management of Bitter Gourd (Momordica Charantia L) in Relation to Pest and disease incidence - Rekha C R (Department of Olericulture, College of Horticulture, 1999)
Investigation on "Nutritional management of bitter gourd (Momordica charantia L.) in relation to pest and disease incidence" was conducted at the College of Horticulture, Kerala Agricultural University, Vellanikkara, Thrissur during kharif (May to October 1997), rabi (September 1997 to January 1998) and Summer (January to May] 998) seasons, by using the variety Preethi. The different sources levels and frequencies of application of organic manures and inorganic fertilizers, constituting eight treatments did not effect significantly on the occurrence of pests like fruit fly (Bactrocera cucurbitae), jassids (Empoasca mottiy, epilachna beetle (Henosepilachna septima) and diseases like mosaic and downy mildew (Pseudoperenospora cubensisi. Seasonal influence was observed on the occurrence of above pests and diseases. Among the pests and diseases affecting the crop, mosaic disease and jassids caused drastic reduction in the crop growth and productivity. Fruit fly infestation was at its peak during rainy season while epilachna beetle and downy mildew during rabi season. Incidence of jassids and intensity of mosaic was maximum during summer season. Productivity of the crop (12.1 t ha-1) and size of fruits in terms of weight (247.58 g) length (23.61 cm) and girth (17.l3 cm) was maximum during rabi season. The treatment T7 which received 20 t ha-1 of FYM, 2.5 t ha-1 of poultry manure, 2.5 t ha-1 of fresh cowdung slurry drenching with NPK @ 70:25:50 kg ha-1 had maximum productivity with maximum fruit size in all the three seasons. Yield in T, which received 20 t ha-1 of FWM as basal and 2.5 t ha-1 of poultry manure at vining stage and 2.5 t ha-1 cowdung slurry drenching at fortnightly interval was double than that in T I which received 25 t ha-1 of FYM only.